2018
DOI: 10.1186/s13104-018-3588-y
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Integrated Management of Newborn and Childhood Illness (IMNCI) in Shire Governmental Health Institution in 2017

Abstract: ObjectiveIn an effort to reduce infant mortality and morbidity, the World Health Organization and other technical partners developed the Integrated Management of Newborn and Childhood Illness (IMNCI). This study focuses on assessment of consistency and completeness of integrated management of neonatal and child hood illness in primary health care units.ResultsA total of 384 cases were taken from 3562 cases both from young infant registration (under-2 month old) and child registration (2 months–5 year old). Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
10
2
Order By: Relevance
“…In our study, the consistency of treatment of childhood illness with the classification of disease at the pre- and postintervention was 48.9 and 85.2%, respectively. The finding was higher than a study conducted in Benin, which showed about 63.6% [ 23 ], and in the Shire, northern Ethiopia, about 42.7% [ 20 ] of the children treated according to IMNCI guideline. The possible difference might be the difference in the performance of individual health workers and skills to manage a sick child using the IMCI guideline.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…In our study, the consistency of treatment of childhood illness with the classification of disease at the pre- and postintervention was 48.9 and 85.2%, respectively. The finding was higher than a study conducted in Benin, which showed about 63.6% [ 23 ], and in the Shire, northern Ethiopia, about 42.7% [ 20 ] of the children treated according to IMNCI guideline. The possible difference might be the difference in the performance of individual health workers and skills to manage a sick child using the IMCI guideline.…”
Section: Discussioncontrasting
confidence: 58%
“…Our interventional study also showed that consistency in assessing and classifying sick children was 49.4 and 82.5% for pre- and postinterventions, respectively, which was better than that of a study conducted in the Shire, northern Ethiopia, which showed that only 62.8% were correctly classified [ 20 ]. Moreover, this study also indicates higher consistency in assessing and classifying sick children from the research conducted in China, which showed that only 43.8% [ 21 ] and Tanzania 28.4% [ 22 ].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Such incomplete case assessments could lead to misclassification and missed referrals. For example, in Ethiopia, Gerensea and colleagues [34] documented that out of 384 cases, 37.2% were classified incorrectly and 57.3% were wrongly treated. Despite nationwide training and expansion of the program, in their study of 4 sub-Saharan African countries (Namibia, Kenya, Tanzania and Uganda), Krüger and colleagues [35] also reported that HCWs failed to recognize IMCI danger signs and primary symptoms, which are crucial for the succeeding steps in the IMCI algorithm.…”
Section: Quality Of Carementioning
confidence: 99%